Aplikasi Pemilihan Tanaman Hias Menggunakan Metode Weight Product Dan Smart Berbasis Web - Oky Triadi Sampurno; Agung Triayudi; Agus Iskandar (STMIK Budi Darma, 2023)
Ornamental plants are plants with aesthetic and aesthetic values that are used to beautify and beautify the atmosphere of rooms in homes, gardens, office buildings, courtyards, hotels, and restaurants. This is a popular foliage plant trend, and every follower has a different taste. Ornamental plants that are generally very popular are agronema, anthurium, adansoni, calathea, monstera and sansevieria. A decision support system is needed to help identify and find out which ornamental plants are most needed by the community. The method used in this system is the Weight Product (WP) method and the SMART method. The WP method is an analytical method for multi-criteria decision making (MCDM). While the SMART method is a multi-characteristic dynamic strategy. This strategy uses multi-trait decisions to aid decision making when exploring multiple options. All leaders must make choices as indicated by the stated goals. This study produces a system to determine the selection of the best ornamental plants. The comparison of the two methods is expected to be more helpful in selecting ornamental plants to be more targeted. The WP and SMART methods using 10 alternative data show that both methods get accurate and suitable data when applied as a ranking of ornamental plants. Both of these methods have an elective execution score and the results of the weight values applied to each technique